(untitled) (BIRDEM Medical Journal, 2021)
Insulin resistance syndromes are a heterogeneous group of disorders with variable clinical phenotypes, associated with increased blood glucose and insulin levels. A 20-year-old female, diabetic for 12 years, reported with hyperglycemia not responding to high dose of insulin; therefore, insulin dosage was increased but did not lead to appropriate glycemic control. Investigations revealed hyperglycemia (random blood glucose 23 mmol/L) glycosylated hemoglobin (HbA1c) 9.2%. Ultrasonogram of the abdomen showed prominent ovaries with fatty liver. Echocardiography revealed mild mitral, pulmonary and tricuspid regurgitation and pulmonary hypertension. Based on the clinical features, skin changes and the onset of type 2 diabetes mellitus, Rabson-Mendenhall syndrome (RMS) was considered. In last admission, she was admitted for hyperglycemic control and treated with intravenous fluids, insulin infusion, metformin, pioglitazone, linagliptin, hydroxychloroquine, sulphonylurea, antibiotics. There is no complete cure for the condition and the current treatments are difficult and not very promising. BIRDEM Med J 2022; 12(1): 83-87